Assessing knowledge and awareness regarding snakebite and management of snakebite envenoming in healthcare workers and the general population: A systematic review and meta-analysis. - Afsana Afroz; Bodrun Naher Siddiquea; Aishwarya Narendra Shetty; Timothy N W Jackson; Andrew D Watt (PLoS Neglected Tropical Diseases)
Background Snakebite envenoming is a serious and life-threatening medical condition that predominantly affects people living in rural communities across Africa, Asia, and Latin America. As our climate changes, there is a growing concern that negative human-snake interactions will increase. Our ability to prevent and manage snakebite requires effective antivenoms as well as knowledge regarding the prevention and management of snakebite among healthcare workers and affected communities across the globe. This systematic review aims to assess existing levels of knowledge regarding snakebite prevention and management in both healthcare workers and affected communities. Methods This review was conducted on studies reporting quantitative measurements to evaluate knowledge and practice regarding snakebite prevention and management published in major databases between 1 January 2000 and 31 December 2021. Random effects modelling was used to obtain the pooled proportion. Heterogeneity (I2) was tested, and sensitivity analyses performed. Results Out of 3,697 records, 16 studies from 12 countries assessing 7,640 participants were included. Four of the studies were ranked as good quality studies, 9 as fair, and 3 as poor. This study results demonstrated that 56% of the study population answered the knowledge question correctly (95% CI 48% to 63%, p < 0.001). High heterogeneity was observed (I2 = 97.29%), with marginal publication bias (Egger's regression test, p = 0.0814). Participants had relatively higher knowledge concerning use of antivenom as preferred treatment, followed by snakebite prevention, knowledge of signs and symptoms of snakebite, knowledge of first-aid, and knowledge of treatment. Participants had lower knowledge relating to types of snakes and the identification of snakes. Conclusion Adequate knowledge about snakebites and its management among the general population and healthcare workers was 56%. Healthcare workers and communities across Asia showed higher relative knowledge compared to those in Africa and the Middle East. These data suggest that further education is needed in both the general population and among healthcare workers to ensure that appropriate preventative and patient management techniques are being utilised in snakebite endemic regions. Greater local awareness of the risks and appropriate management of snakebite is required to reduce the burden of snakebite mortality and morbidity.